Transdisciplinary systems approach to realization of digital transformation. (August 2021) - Hashmi, Muhammad A.; Mo, John P.T.; Beckett, Ronald C.
Abstract: With advancement in technology and emergence of fast networks, operation of businesses and global companies increasingly depend on the Internet and digital transformation of their infrastructures. Adaptation to Industry 4.0 paradigm gives rise to societal, technological and communication issues due to challenges in product, services, social and inter-disciplinary interactions. A more fundamental approach that can mitigate complexity of the new business is necessary. This paper adopts a system of systems model embedded into a transdisciplinary system design to describe a typical X4.0 system where X can be any industry sector migrating to Industry 4.0 paradigm. Two industry sectors: Education 4.0 and Retail 4.0 are studied under the amalgamated transdisciplinary system of systems model. Results show that the four artifacts in X4.0 can form the foundation of new sectorial 4.0 development with focus on specific elements in Cyber Physical Systems and Work4.0 artifacts. The transdisciplinary system approach has the advantage of a self-improving model that drives realization of digital transformation in evolutionary cycles.